2014
DOI: 10.1001/jama.2014.13204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Vitamin D3on Hospital Length of Stay in Critically Ill Patients With Vitamin D Deficiency

Abstract: clinicaltrials.gov Identifier: NCT01130181.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
407
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(464 citation statements)
references
References 29 publications
21
407
2
9
Order By: Relevance
“…An intervention trial of calcitriol therapy in critically ill adults with sepsis did not have an impact on the primary outcome, antimicrobial peptide levels (29). A recent trial of high-dose vitamin D3 repletion in deficient critically ill adults did not show an impact on mortality or length of stay, except for subjects with the lowest 25(OH)D levels (,12 ng/ml) (30). The severely 25(OH)D-deficient group that was treated had lower mortality at 28 days after ICU admission, at hospital discharge, and at 6 months later (30).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 96%
“…An intervention trial of calcitriol therapy in critically ill adults with sepsis did not have an impact on the primary outcome, antimicrobial peptide levels (29). A recent trial of high-dose vitamin D3 repletion in deficient critically ill adults did not show an impact on mortality or length of stay, except for subjects with the lowest 25(OH)D levels (,12 ng/ml) (30). The severely 25(OH)D-deficient group that was treated had lower mortality at 28 days after ICU admission, at hospital discharge, and at 6 months later (30).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 96%
“…As in the total group no outcome effects were demonstrated that this may potentially imply that some patients also may have had some negative effects of the supplementation, although this cannot directly be concluded from the published data. For the total group, supplementation does not seem to be warranted, possibly only for those patients with severe deficiency (26).…”
Section: Vitamin D Deficiency In the Critically Illmentioning
confidence: 99%
“…Amrein and coworkers showed a survival benefit of supplementation in severely deficient patients (26).…”
Section: Vitamin D Deficiency In the Critically Illmentioning
confidence: 99%
“…In support of this, many studies report that vitamin D supplementation in critically ill patients is associated with decreased mortality (27,28). Conversely, in the VITdAL-ICU study, administration of high dose vitamin D compared with placebo did not reduce hospital length of stay, hospital mortality, or 6-month mortality (29). We found that the median APACHE II score and number of organ dysfunction were 28 and 2, respectively, in 38 non-survivor patients with low vitamin D level even though vitamin D had been administered to them, and they were 27.5 and 3 in 8 non-survivor patients with normal vitamin D level.…”
Section: Discussionmentioning
confidence: 94%